The effect of low-level light therapy on orthodontic tooth movement rate, heat shock protein 70, and matrix metallopreteinase 8 expression: Animal study - Ida Bagus Narmada; Muhammad Rubianto; Suhartono Taat Putra (Wolters Kluwer Medknow Publications, 2020)
Background: The aim of this study was to determine the effect of low-level light therapy (LLLT) on orthodontic tooth movement (OTM) rate, heat shock protein 70 (HSP-70) expression, and matrix metalloproteinase 8 (MMP-8) expression. Materials and Methods: In this experimental study twenty-four male guinea pigs were randomly divided into three groups (n = 8): control group (K) without orthodontic force and LLLT; treatment group 1 (T1) with orthodontic force, and treatment group 2 (T2) with orthodontic force and LLLT. The labial surfaces of both maxillary central incisors in treatments groups were installed with single-wing bracket before being inserted with close coil spring to give 10 g/cm2 orthodontic force. For the T2 group, 4 J/cm2 of LLLT was administered in the mesial-distal and labial-palatal regions for 3 min every day. On day 14, the gap between teeth was measured and immunohistochemistry staining was done to determine HSP-70 and MMP-8 expression. Data were analyzed using (IBM, New York, (ANOVA), followed by Turkey's HSD test to determine the differences between groups. Nonnormal distributed data would be analyzed using Kruskal-Wallis test, followed by Mann-Whitney test with P < 0.05 being performed. Results: The gap between teeth in the T2 group was greater compared to T1 group (P = 0.00). However, there was a significant decrease of HSP-70 and MMP-8 expression in T2 group compared to T1 group in the tensile and compressive sides. Conclusion: LLLT intervention during orthodontic treatment could accelerate OTM rate and decreased HSP-70 and MMP-8 expression both in tension and in compressive side. Thus, LLLT interventions can be used as adjuvant therapy to shorten orthodontic treatment duration.